Comparative study of four aortic allograft decellularization techniques - Shchatsinka, M. M.; Spirydonau, S. V.; Adzintsou, V. A.; Shket, A. P.; Yudzina, V. A.; Smaliakova, R. M.; Suboch, A. I.; Dryk, S. I.; Yurkshtovich, M. K.; Ostrovsky, Y. P. (Ukrainian Journal of Cardiovascular Surgery, 2017)
Objective: to assess four aortic allograft decellularization techniques. Materials and methods. 40 aortic allografts were decellularized using 4 techniques (n=10 in each group), depending on reagents used: 1) 1% deoxycholic acid; 2) 0,5% sodium deoxycholate, 0,5% sodium dodecylsulfate; 3) 1% sodium deoxy-cholate, 1% Triton X-100; 4) 3% Triton X-100, 0.04% EDTA. On decellularization completion, specimens were subjected to histologic (hematoxylin and eosin) and histochemic (MSB, orcein) studies; residual DNA content was assessed, as well as mechanical testing. Results and discussion. Decellularization with 0.5% sodium deoxycholate, 0.5% sodium dodecylsulfate resulted in com-plete cell removal with good preservation of connective tissue matrix. Statistically significant reduction of DNA content in aorta (31,05 vs 2,58 ng/mg, p<0,01) and aortic valve leaflet (39,7 vs 1,36 ng/mg, p<0,05) was revealed. According to mechanical testing results, there were no significant differences between fresh, cryopreserved and decellularized allografts. Conclusions. Complete allograft decellularization was achieved using 0.5% sodium deoxycholate, 0.5% sodium dodecy-lsulfate, with statistically significant DNA reduction and without affecting mechanical properties of the valve.